MINIMAL INVASIVE FOR MAXIMAL RECOVERY IN DENTAL TRAUMA : A CASE REPORT - Anak Agung Manik Swayoga; Ilma Yudistian (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Dentoalveolar fractures can be treated in a simple non-surgical procedure by repositioning the fractured fragments and immobilizing them. One of the factors affecting the success of dentoalveolar fracture treatment is the choice of material and immobilization technique. Case: A 16-year-old girl came to the Emergency Department with complaints of bleeding from the mouth due to a traffic accident 5 hours ago. Her lip hit the handlebar of a motorcycle. There was no history of fainting, vomiting, and bleeding from the ears and nose. Extraoral examination revealed an asymmetrical face. Edema and laceration on the upper lip. Intraoral examination revealed gingival laceration of teeth 12-22 and avulsion of teeth 12,22. Panoramic x-ray revealed supra position of teeth 11, 21 and avulsion of teeth 12, 22. Case Management: Wound debridement, indirect root canal treatment of teeth 12, 22, repositioning of teeth 12-22, fixation with wire and composite splinting, selective grinding, antibiotics, and analgesics were performed. Post-operative instructions included maintaining oral hygiene, a soft diet, and a return for splinting control. Discussion: The goal of dentoalveolar trauma treatment is to restore the normal function and shape of the masticatory organs. The treatment in this case uses flexible splinting because it has ability to resemble the physiological mobility condition of the teeth which can help the healing of the periodontal ligament. The treatment results showed soft and hard tissue healing after one month of treatment. Conclusion: Successful treatment of dentoalveolar fractures will be achieved if performed promptly and if accurate immobilization and accurate tools are used. Simple tools and techniques make flexible splinting a good treatment for simple dentoalveolar fractures.